The part-time pay penalty for women in Britain - Alan Manning; Barbara Petrongolo (Institute for the Study of Labor (IZA), 2006)
Women in Britain who work part-time have, on average, hourly earnings about 25% less than that of women working full-time. This gap has widened greatly over the past 30 years. This paper tries to explain this part-time pay penalty. It shows that a sizeable part of the penalty can be explained by the differing characteristics pf FT and PT women. Inclusion of standard demographics halves the estimate of the pay penalty. But inclusion of occupation makes the pay penalty very small, suggesting that almost the entire unexplained gap is due to occupational segregation. The rise in the pay penalty over time is partly a result of a rise in occupational segregation and partly the general rise in wage inequality. Policies to reduce the pay penalty have had little effect and it is likely that it will not change much unless better jobs can be made available on a part-time basis.
urn:nbn:de:101:1-2009030992
Keywords: 330